SOFT SKILL BAGI GURU DALAM PENDIDIKAN ISLAM - Alex Yusron Al Mufti (Universitas Islam Nahdlatul Ulama Jepara, 2016)
ABSTRACTThe ASEAN Economic Community (MEA) is one of the opportunities and challenges for Indonesia in facing this century of Asian economy. Indonesia has no choice to get involved in the globalization process and the increasingly competition in various fields. MEA will have an impact on the integration of the economic sector, even the education sector will also be affected by the possibility of foreign educational institutions which open classes of higher quality education in Indonesia. Business actors and academics are required to be able to formulate standards of professional competence in each sector. Efforts to improve the quality of human resources can be pursued by synergizing with the government. Improvement of the quality of human resources by improving teachers?? ability on soft skill in Islamic education is very important to compete in facing the MEA, which in turn can have result in quality education. Without a quality education, the hope of creating professional skilled qualified human resources will only be a hope. Keywords: Soft skill, Teachers, Islamic Education.